Toxic leadership in higher education: Lived xperiences of academics in South African universities - Nendauni, L.; Ravhuhali, F. (South African Journal of Higher Education, 2026)
Leadership in higher education plays a crucial role in shaping the success and sustainability of academic institutions. However, the phenomenon of toxic leadership, which is characterised by destructive behaviours such as manipulation, narcissism, and authoritarianism, can severely undermine the effectiveness and well-being of individuals and institutions. This article investigates the lived experiences of academics under toxic leadership in South African universities, a context where little research has been done on toxic leadership. Drawing on qualitative data collected from five academics through open-ended questionnaires, this article examines the specific toxic behaviours encountered, their impacts on professional and personal lives, and the coping strategies employed by the affected academics. The findings of this article reveal that toxic leadership in South African universities is marked by behaviours including micromanagement, favouritism, and erratic decision-making. These behaviours contribute to stress, burnout, decreased job satisfaction, and impaired professional relationships among academics. This article accentuates the need for improved leadership development, grievance mechanisms, and regular evaluations of leadership practices to create healthier academic environments. Further research is suggested to assess the long-term impact of toxic leadership and its intersection with demographic factors.